2020
DOI: 10.1037/edu0000395
|View full text |Cite
|
Sign up to set email alerts
|

What’s the best way to characterize the relationship between working memory and achievement?: An initial examination of competing theories.

Abstract: Although studies have demonstrated a relationship between working memory and achievement in math and reading, it is still unclear why working memory might be related to these abilities. In the present article, we examined the viability of several possible theories in 2 separate analyses of math and reading. In each case, we contrasted the predictions of a cognitive filter model, a transactional model, and a positive manifold model using data from the 2011 Early Childhood Longitudinal Study Kindergarten (ECLS-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 65 publications
(94 reference statements)
4
42
1
Order By: Relevance
“…The inconsistent pattern of findings in our replication study mimic the inconsistencies that are found in the EF and academic skills literature during early childhood. In addition to the results reported by Schmitt et al (2017), several recent studies have also found evidence of the co-development of EF and academic achievement (e.g., Cameron et al, 2019;McKinnon & Blair, 2019;Meixner et al, 2019;Miller-Cotto & Byrnes, 2020;Welsh et al, 2010). However, others (Fuhs et al, 2014;Willoughby et al, 2019), including the current replication have demonstrated that EF prospectively predicts academic skills, which is inconsistent with the theory of mutualism between cognitive and academic skills across early development (e.g., Peng & Kievit, 2020).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The inconsistent pattern of findings in our replication study mimic the inconsistencies that are found in the EF and academic skills literature during early childhood. In addition to the results reported by Schmitt et al (2017), several recent studies have also found evidence of the co-development of EF and academic achievement (e.g., Cameron et al, 2019;McKinnon & Blair, 2019;Meixner et al, 2019;Miller-Cotto & Byrnes, 2020;Welsh et al, 2010). However, others (Fuhs et al, 2014;Willoughby et al, 2019), including the current replication have demonstrated that EF prospectively predicts academic skills, which is inconsistent with the theory of mutualism between cognitive and academic skills across early development (e.g., Peng & Kievit, 2020).…”
Section: Discussioncontrasting
confidence: 91%
“…Recent work, however, has cast doubt on the causal links between early EF skills and children's academic development (e.g., Jacob & Parkinson, 2015). Longitudinal studies, for example, examining bidirectional links between EF skills and academic achievement have challenged the predominant unidirectional perspective of EF supporting academic skill development (e.g., Cameron, Kim, Duncan, Becker, & McClelland, 2019;Fuhs, Nesbitt, Farran, & Dong, 2014;McKinnon & Blair, 2019;Meixner, Warner, Lensing, Schiefele, & Elsner, 2019;Miller-Cotto & Byrnes, 2020;Welsh, Nix, Blair, Bierman, & Nelson, 2010). This work has leveraged the availability of multiple time-points of data to describe reciprocal relations between EF and achievement over time, testing whether these constructs co-develop or are directional in nature during the early years of schooling.…”
Section: Executive Function and Academic Achievementmentioning
confidence: 99%
“…Running head: ACADEMIC ACHIEVEMENT AND COGNITION 8 Specifically, using cross-lagged modelling on a large data sample from the Early Childhood Longitudinal Study, Kindergarten (ECLS-K), Miller-Cotto and Byrnes (2019) found that working memory and reading/mathematics significantly predicted each other from the beginning of kindergarten through second grade. Schmitt, Geldhof, Purpura, Duncan, and McClelland (2017) Ferrer and colleagues (Ferrer et al, 2007;Ferrer, Shaywitz, Holahan, Marchione, & Shaywitz, 2010) Intervention effects.…”
Section: Bidirectionality: Cognitive Abilities ↔ Academic Achievementmentioning
confidence: 99%
“…Similar reciprocal effects, where the development of a given academic skill predicts growth in cognitive performance and vice-versa, have been reported between working memory and reading and maths (Miller-Cotto & Byrnes, 2019), IQ and reading (Ferrer et al, 2007(Ferrer et al, , 2010, nonverbal reasoning and vocabulary (Kievit et al, , 2019, and executive functions and maths (Schmitt et al, 2017). These examples suggest that difficulties in one domain may have downstream effects on other abilities, and challenge the use of analytic strategies in which cognitive deficits are uniquely modelled as predictors and academic skills as outcomes.…”
Section: Bidirectional Dynamicsmentioning
confidence: 54%